Adsorpsi Ion Logam Tembaga Menggunakan Karbon Aktif dari Bahan Baku Kulit Salak - Febe Apecsiana; Hans Kristianto; Arenst Andreas (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Heavy metals contained inside water may carry negative impacts to humans and environment. The most effective treatment is adsorption using activated carbon which is obtained through chemical activation of snake fruit peel using KOH compound. The ratio of snake fruit peel to KOH (20%-w solution) used was 1:4. Snake fruit peel activated carbon with surface area of 2526 m2/g were obtained. The content of heavy metal ions (Cu2+) in the water were analyzed using spectrophotometer UV-Vis with NH3(p.a) solution which form a complex bound colored dark blue. Investigation was carried out by studying the influence of initial concentration (100, 150, 200, 250, and 300 ppm), pH (2,5; 3,5; 5), the amount of adsorbent (30, 60, 90 mg), dan temperature (25oC, 35 oC, dan 45 oC ) to obtain optimum condition with the highest %removal at initial concentration 100 ppm, pH 5, 90 mg adsorbent, and there's no significant differences by varying temperature. Adsorption isotherm studies indicated that Langmuir model fit better with maximum adsorption capacity of 687 mg/g and Langmuir constant for the variation of initial concentration and the amount of adsorbent were 0.0473 L/mg and 0.0296 L/mg, respectively. The kinetics of adsorption of Cu(II) followed pseudo second order.